Crossroads Corpus creation: Design and case study - Hantgan-Sonko, Abbie (Yearbook of the Poznan Linguistic Meeting, 2017)
This paper illustrates a methodological approach to the design of an annotated corpus using a case study of phonetic convergences and divergences by multilingual speakers in southwestern Senegal’s Casamance region. The newly compiled corpus contains approximately 183,000 annotations of multilingual, spoken data, gathered by eight researchers over a ten year span using methods ranging from structured lexical elicitation in controlled contexts to naturally occurring, multilingual conversations. The area from which the data were collected consists of three villages and their primary languages, and yet many more contribute to the linguistic landscape. Detailed metadata inform analyses of variation, the context in which a speech act took place and between whom, the speakers’ linguistic repertoires, trajectories, and social networks, as well as the larger language context. A potential path for convergence or divergence that emerged during data collection and in building and searching the corpus is the crossroads in the phonetic production of word-initial velar plosives. Word-initial [k] emerges in one language where only [ɡ] is present in the other; the third utilizes both. The corpus design makes it feasible, not only to identify areas of accommodation, but to grasp the context, enabling a sociolinguistically informed analysis of the speakers’ linguistic behavior.